Search for a Standard Model Higgs Boson in the H -> ZZ -> l(+)l(-)v(v)over-bar Decay Channel with the ATLAS Detector - Onofre, A. (2011)
A search for a heavy standard model Higgs boson decaying via H→ZZ→ℓ+ℓ−ν¯ν, where ℓ=e, μ, is presented. It is based on proton-proton collision data at √s=7  TeV, collected by the ATLAS experiment at the LHC in the first half of 2011 and corresponding to an integrated luminosity of 1.04  fb−1. The data are compared to the expected standard model backgrounds. The data and the background expectations are found to be in agreement and upper limits are placed on the Higgs boson production cross section over the entire mass window considered; in particular, the production of a standard model Higgs boson is excluded in the region 340<mH<450  GeV at the 95% confidence level.